AN ANALYSIS OF FACTORS INFLUENCING STUDENT’S INTEREST IN LEARNING ENGLISH AT GRADE X MA AL MUNAWWAROH RAMBAH HILIR - Ummi Rasyidah; Pipit Rahayu; Eripuddin Eripuddin; Syafrina Syafrina (English Study Program University of Pasir Pengaraian, 2025)
This research aims to analyze the factors that influence students' interest in learning English in class X MA Al Munawwaroh. This research uses qualitative methods by collecting data through interviews aimed at class X MA Al Munawwaroh student teachers. The research results show that the factors that influence students' interest in learning English are motivation, English language skills, and the learning environment. Students' motivation to learn English is influenced by the desire to improve English language skills, expand knowledge, and increase career opportunities. Students' English language skills also influence their interest in learning English, because students who have English skills are more interested in learning English. A conducive and enjoyable learning environment also influences students' interest in learning English. This research concludes that to increase students' interest in learning English, efforts need to be made to increase student motivation, English language skills, and a conducive learning environment.